(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
This article provides a comprehensive analysis of the essence of the concept of human capital and its impact on the socio-economic development of society. The study examines the main strategic directions for the development of human capital, including the improvement of the education system, the advancement of healthcare, the enhancement of skills and competencies, and investment through innovative and digital technologies. In addition, the socio-economic effects of investments in human capital on labor productivity, economic growth, and social well-being are theoretically substantiated. Based on an analysis of global and national experiences, the article reveals the role of human capital in ensuring sustainable development and highlights effective mechanisms for managing human resources in both developed and developing countries. Furthermore, the interconnection between the education system, the labor market, and digital transformation processes is examined as a key factor in the formation and development of human capital. The research findings have significant scientific and practical value for the development of effective strategies for investing in human capital.